The Effect of CEO Tenure, CFO Education Level, Board Gender Diversity, and Other Comprehensive Income on Earnings Management - Kurniawati, May Mulan; Abbas, Dirvi Surya; Hidayat, Imam (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the effect of CEO tenure, Chief Financial Officer (CFO) education level, board gender diversity, and other comprehensive income (OCI) on earnings management practices, considering high and low Corporate Governance Perception Index (CGPI) conditions. The research sample consisted of 210 public companies in Indonesia during the period 2020–2024. The analysis method used was panel data regression with a fixed effect model (FEM) approach based on the results of the Chow, Hausman, and Lagrange Multiplier tests. The results show that CEO tenure has a negative and significant effect on earnings management, CFO education level has a negative but not significant effect, board gender diversity has a negative and significant effect, and OCI has a positive and significant effect on earnings management. Companies with high CGPI scores tend to show lower levels of earnings management compared to companies with low CGPI scores. These findings reinforce the importance of executive characteristics and corporate governance in controlling opportunistic financial reporting behavior.